Relevance of systematic anti-nuclear antibodies testing after obstetrical complications. (November 2021) - Koubi, Marie; Rossi, Pascal; Arcani, Robin; Gomes De Pihno, Quentin; Chau, Cecile; Blanc, Julie; Grosdidier, Charlotte; Guervilly, Christophe; Bretelle, Florence; Bernard-Guervilly, Fanny
Highlights: Determination of ANA after any obstetrical event may be routinely considered. ANA positivity with obstetrical event should be referred to reference center. ANA discovery was associated to a diagnosis of AID in 12.4 %. Collaboration between obstetricians and specialists allow early detection of AID. Early detection of AID reduces negative impacts on subsequent pregnancies. Abstract: Adverses pregnancy outcomes are commonly encountered with autoimmune disease (AID). Although anti-nuclear antibodies (ANA) are often present several years before AID diagnosis, the importance of ANA testing has not been evaluated in this context. The objective of this study was to determine if ANA discovery after obstetrical complications is associated with a diagnosis of AID and improves the prognosis of subsequent pregnancies. All patients presented at the multidisciplinary board meeting (MBM) "Thrombophilia and Pregnancy", whose ANA were discovered after an obstetrical complication, were included in a multicenter descriptive study. All patients were referred to an internal medicine consultation for diagnosis. Data were collected retrospectively by computer chart analysis and updated by phone. A total of 404 patients were included, of which 50 (12.4 %) had a diagnosis of AID related to ANA. Patients with AID had higher ANA levels (p < 0.001), with more frequent specificity (26%, versus 6.7%, p < 0.0001), and more often persistent (84% versus 30.8%, p < 0.0001) compared to patients without AID. Subsequent pregnancy outcomes were not significantly affected by ANA levels and AID diagnoses. Our study shows that the discovery of ANA after obstetrical complications may lead to an early diagnosis of AID. It makes us reconsider the systematic determination of ANA after an obstetrical event because in the case where ANA are found positive, an adapted follow-up would reduce the negative impact of ANA presence on subsequent pregnancies.